HEAT CONDUCTION IN MOVING SOLIDS USING GREEN’S FUNCTION - Ribeiro, S. S.; Guimarães G.; Fernandes, A.; Oliveira, G. C. (Revista de Engenharia Térmica, 2015)
Thermal problems involving moving heat sources occur in various engineering applications, such as welding processes, heat treatment furnaces and other treatments. Typically, in these cases, the precise formulation of the numerical solution due to the high complexity of the heat diffusion governing equation, boundary condition, including convection terms. This work proposes a mathematical analysis, analytical solution, verification using other solutions and comparison with numerical solution of a 1D transient thermal model based on Green’n functions, considering a solid moving at a constant speed along a cartesian coordinated.